2009
DOI: 10.20506/rst.28.1.1861
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination as a tool to combat introductions of notifiable avian influenza viruses in Europe, 2000 to 2006

Abstract: In late 2000, Italy was the first country of the European Union (EU) to implement an emergency vaccination programme against notifiable avian influenza. Vaccination with a conventional vaccine containing a seed strain with a different neuraminidase subtype from that of the field virus was used to complement biosecurity and restriction measures as part of an overall eradication strategy. This vaccination technique, in line with the Differentiating Infected from Vaccinated Animals system (DIVA), was applied seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The incursion of any BTV strain (even a vaccine strain) into a BTV-free area is currently treated as an outbreak by regulatory agencies, with restrictions on animal movements and trade. Thus, by better understanding the determinants of BTV virulence, we may be able to design control strategies that "fit" the risks posed by specific incursions, using an approach similar to that taken for avian influenza or Newcastle disease (1,20).…”
Section: Discussionmentioning
confidence: 99%
“…The incursion of any BTV strain (even a vaccine strain) into a BTV-free area is currently treated as an outbreak by regulatory agencies, with restrictions on animal movements and trade. Thus, by better understanding the determinants of BTV virulence, we may be able to design control strategies that "fit" the risks posed by specific incursions, using an approach similar to that taken for avian influenza or Newcastle disease (1,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, a carefully conceived vaccination strategy must be accompanied by strict bio-security measures and efficient monitoring systems. Countries which have authorized vaccination to control avian influenza outbreaks under special circumstances in the past have met with contradictory results, from effective control and disease eradication to antigenic drift of the viral strain (Lee et al, 2004; Busani et al, 2009; Capua et al, 2009). Extensive vaccination programs are currently ongoing in South East Asia and Egypt to control the H5N1 HPAI epidemics (Peyre et al, 2009; Domenech et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Antibody titres against influenza were also highly variable in a post-vaccination surveillance study in France in 2006. Following vaccination with an inactivated H5N2 vaccine in free-range domestic ducks, sera were collected in flocks where unvaccinated sentinel birds had remained negative and were tested against the vaccinal antigen: HI titres ranged between 0 and 9 log 2 with a mean titre of 6 log 2 [28]. Other experimental studies have shown that vaccination against influenza in ducks with inactivated vaccines eventually requires higher antigen doses and multiple injections to be immunogenic and protective [29].…”
Section: Dedicationmentioning
confidence: 99%